МЕТОДЫ СНИЖЕНИЯ МАГНИТНОГО ПОЛЯ ВОЗДУШНЫХ ЛИНИЙ ЭЛЕКТРОПЕРЕДАЧИ ЗА ПРЕДЕЛАМИ ОХРАННЫХ ЗОН - Пелевин, Д.Е. (Інститут електродинаміки НАН України, Київ, 2014)
The prolonged action on the population of the magnetic field at 50 (60) Hz low intensity (with induction 0.2-0.5 mT) is more dangerous than the effect of the electric field. This explains the global trend of tightening health standards concerning the magnetic field (MF). The results of studies of MF induction of overhead power lines (OPL) with voltage 0.4-330 kV are presented. They show a dangerous exceeding of the level 0.5 μT in 1.4-6 times beyond the existing security zone of the OPLs. Theoretically grounded methods of reducing MF in residential buildings. These methods are: the expansion of security zones OPLs, shielding, reducing of MF OPL (decrease the distance between the phase conductor, providing compensation of MF by splitting of conductors phases). The practical implementation of methods to reduce the MP to a safe level has been determined. References 10, figures 2.